Rancang Bangun Portal Business Partner Berbasis Website Pada PT Properti Solusi Manajemen - Sari, Yunita; Reinardi, Aldo Davin (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Along with the increasingly rapid development of information technology, humans are trying to create equipment and systems that can simplify the data processing process and convey information to produce a picture of data or information that is accurate and easy to understand. In carrying out relationships between Business to Business (B2B) or Business to Consusmer (B2C), companies need potential business partners who can work together to create efficiencies and opportunities. PT Properti Solusi Manajemen is a start-up company in the Property sector which has a daily service provision sub-service with the product name Pinhome Service. Pinhome Service is here to make it easier to access cleaning and maintenance services for homes, electronic equipment, vehicles and massage services. The partnership system implemented has made PT Properti Solusi Manajemen feel the need for information transparency between both parties. Therefore, PT Properti Solusi Management needs an information system that can be used to convey information regarding certain data to Business Partners in order to create a good relationship between PT Properti Solusi Management and Business Partners.